2015
DOI: 10.1007/s00128-015-1698-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations of Taste and Odor Compounds in Surface Water, Overlying Water and Sediment of the Western Lake Chaohu, China

Abstract: The seasonal variations of taste and odor (T&O) compounds in western Lake Chaohu were evaluated from July to December 2013. High values were detected in particulate fractions, with peak values 28.25 ng/L for geosmin (GEO), 45.18 ng/L for dimethyltrisulfide (DMTS), 714.77 ng/L for β-cyclocitral, 11.23 ng/L for β-ionone in surface water, and 14.21 ng/L for GEO, 103.68 ng/L for DMTS, 11.97 ng/L for β-ionone in overlying water, all exceeding their odor thresholds. The maximum off-flavor concentrations in sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…2(A) and (B)) as many results report peak concentrations of T&O in this month. [17][18][19] In September 2009, the concentration of b-ionone (58.62-1932.73 ng L À1 ) was the highest among all the investigated T&O compounds, which is a major off-avor metabolite of M. aeruginosa 15,24 and a product of carotene (also an important metabolite of Microcystis aeruginosa) oxidation when it is exposed to oxygen gas. 25 An earlier study also identied it as a T&O compound in lake water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2(A) and (B)) as many results report peak concentrations of T&O in this month. [17][18][19] In September 2009, the concentration of b-ionone (58.62-1932.73 ng L À1 ) was the highest among all the investigated T&O compounds, which is a major off-avor metabolite of M. aeruginosa 15,24 and a product of carotene (also an important metabolite of Microcystis aeruginosa) oxidation when it is exposed to oxygen gas. 25 An earlier study also identied it as a T&O compound in lake water.…”
Section: Resultsmentioning
confidence: 99%
“…This result is partly consistent with the correlation analysis results (Table 2) and other observed data. 18 Moreover, other authors also found that geosmin and UV254 were part of the same group using PCA to analyze the occurrence of T&O. 15 Group 2 was made of IPMP, IBMP, 2-MIB, b-ionone and bcyclocitral, which indicate that T&O compounds were one of the major components in all the water parameters.…”
Section: Multivariate Analysis Between Tando and Water Qualitymentioning
confidence: 92%
See 2 more Smart Citations
“…The lake has been heavily polluted and suffered from increasing harmful algal blooms since the 1990s. Although several algae species have been observed, cyanobacterial blooms commonly occur from May to November of each year throughout the lake [63,64]. The lake is commonly divided into three parts based on their eutrophication levels; the western part is in severely eutrophic status while the central and eastern parts are considered to be mesotrophic.…”
Section: Study Sitementioning
confidence: 99%